2020
DOI: 10.5483/bmbrep.2020.53.2.264
|View full text |Cite
|
Sign up to set email alerts
|

Methylated-UHRF1 and PARP1 Interaction Is Critical for Homologous Recombination

Abstract: A recent study suggested that methylation of ubiquitin-like with PHD and RING finger domain 1 (UHRF1) is regulated by SET7 and lysine-specific histone demethylase 1A (LSD1) and is essential for homologous recombination (HR). The study demonstrated that SET7-mediated methylation of UHRF1 promotes polyubiquitination of proliferating cell nuclear antigen (PCNA), inducing HR. However, studies on mediators that interact with and recruit UHRF1 to damaged lesions are needed to elucidate the mechanism of UHRF1 methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…In specific conditions, the same residue can be differentially modified to obtain diverse outcomes, e.g. methylation of K385 by SET7 confers the ability to promote DNA repair by homologous recombination during S phase ( 72 , 73 ), while methylation of the same residue by SET8 during G2 mediates UHRF1 destabilization and degradation ( 74 ). UHRF1 can perform auto-ubiquitination via the intrinsic ubiquitin E3 ligase activity of its RING domain ( 5 , 75 ).…”
Section: Uhrf1: Epigenetic Functions and Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In specific conditions, the same residue can be differentially modified to obtain diverse outcomes, e.g. methylation of K385 by SET7 confers the ability to promote DNA repair by homologous recombination during S phase ( 72 , 73 ), while methylation of the same residue by SET8 during G2 mediates UHRF1 destabilization and degradation ( 74 ). UHRF1 can perform auto-ubiquitination via the intrinsic ubiquitin E3 ligase activity of its RING domain ( 5 , 75 ).…”
Section: Uhrf1: Epigenetic Functions and Regulationmentioning
confidence: 99%
“…Accumulation at stalled forks of RAD18-dependent mono-ubiquitinated PCNA was demonstrated to direct the repair towards the process of ICL resolution ( 107 ). All the aforementioned factors are very well-known interactors of UHRF1; many have been directly associated with UHRF1 in DNA damage ( 72 , 73 ), while others are still being evaluated. Among the latter, the interaction between the MYST domain of TIP60 and the SRA and RING domains of UHRF1 ( 47 ) is peculiar because UHRF1 is commonly associated to DNA methylation and heterochromatin formation, two processes that are not expected to be associated with histone acetylation, generally linked to chromatin relaxation and activation of transcription.…”
Section: Uhrf1 At the Crossroad Between Epigenome Maintenance And Genome Integrity Preservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we have identified that SET7-mediated UHRF1 methylation in response to DNA damage, polyubiquitinates PCNA, and promotes HR progression ( 13 ). We also reported that PARP1 is required for the recruitment of methylated UHRF1 to DNA damage sites and for the HR repair pathway ( 28 ). Several studies have indicated that SET7 is also involved in the regulation of PARP1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…PARylation seems to be required for the maintenance of heterochromatin throughout cell divisions by controlling UHFR1-DNMT1 interplay and by directing DNMT1 to euchromatin regions and hemi-methylated CpG dyads [ 97 ]. The interaction of UHRF1-PARP1 seems also essential for cell viability, as recent findings suggest its involvement in response to DNA damage [ 98 ].…”
Section: Other Cross-talks In the Complex Network Created By Parpmentioning
confidence: 99%